Disbalancing Envelope Stress Responses as a Strategy for Sensitization of Escherichia coli to Antimicrobial Agents - Recacha, Esther; Fox, Valeria; Díaz-Díaz, Sara; García-Duque, Ana; Docobo-Pérez, Fernando; Pascual, Álvaro; Rodríguez-Martínez, José Manuel (Frontiers in Microbiology, 2021)
Disbalancing envelope stress responses was investigated as a strategy for sensitization of Escherichia coli to antimicrobial agents. Seventeen isogenic strains were selected from the KEIO collection with deletions in genes corresponding to the σE, Cpx, Rcs, Bae, and Psp responses. Antimicrobial activity against 20 drugs with different targets was evaluated by disk diffusion and gradient strip tests. Growth curves and time-kill curves were also determined for selected mutant-antimicrobial combinations. An increase in susceptibility to ampicillin, ceftazidime, cefepime, aztreonam, ertapenem and fosfomycin was detected. Growth curves for Psp response mutants showed a decrease in optical density (OD) using sub-MIC concentrations of ceftazidime and aztreonam (∆pspA and ∆pspB mutants), cefepime (∆pspB and ∆pspC mutants) and ertapenem (∆pspB mutant). Time-kill curves were also performed using 1xMIC concentrations of these antimicrobials. For ceftazidime, 2.9 log10 (∆pspA mutant) and 0.9 log10 (∆pspB mutant) decreases were observed at 24 and 8 hours, respectively. For aztreonam, a decrease of 3.1 log10 (∆pspA mutant) and 4 log1010 (∆pspB mutant) was shown after 4-6 hours. For cefepime, 4.2 log10 (∆pspB mutant) and 2.6 log10 (∆pspC mutant) decreases were observed at 8 and 4 hours, respectively. For ertapenem, a decrease of up to 6 log10 (∆pspB mutant) was observed at 24 hours. A deficient Psp envelope stress response increased E. coli susceptibility to beta-lactam agents such as cefepime, ceftazidime, aztreonam and ertapenem. Its role in repairing extensive inner membrane disruptions makes this pathway essential to bacterial survival, so that disbalancing the Psp response could be an appropriate target for sensitization strategies.